Towards Understanding the Role of Surface Gas Nanostructures: Effect of Temperature Difference Pretreatment on Wetting and Flotation of Sulfide Minerals and Pb-Zn Ore - Yuri Mikhlin; Anton Karacharov; Sergey Vorobyev; Alexander Romanchenko; Maxim Likhatski; Svetlana Antsiferova; Svetlana Markosyan (Nanomaterials, 2020)
Surface nanobubbles at hydrophobic interfaces now attract much attention in various fields but their role in wetting-related phenomena is still unclear. Herein, we report the effect of a preliminary contact of “hot” solids with cold water previously proposed for generation of surface nanobubbles, on wettability of compact materials and flotation of particulate galena (PbS), sphalerite (ZnS), and Pb-Zn sulfide ore. Atomic force microscopy was applied to visualize the nanobubbles at galena crystals heated in air and contacted with cold water; X-ray photoelectron spectroscopy was used to characterize the surface composition of minerals. Contact angles measured with the sessile drop of cold water were found to increase when enhancing the support temperature from 0 to 80 °C for sphalerite and silica, and to pass a maximum at 40–60 °C for galena and pyrite (FeS2) probably due to oxidation of sulfides. The temperature pretreatment depressed the recovery of sulfides in collectorless schemes and improved the potassium butyl xanthate-assisted flotation both for single minerals and Gorevskoye Pb-Zn ore. The results suggest that the surface nanobubbles prepared using the temperature difference promote flotation if minerals are rather hydrophobic and insignificantly oxidized, so the addition of collector and activator (for sphalerite) is necessary.